The Drosophila GAGA factor is required for dosage compensation in males and for the formation of the male-specific-lethal complex chromatin entry site at 12DE. - Greenberg, A.J.; Yanowitz, J.L.; Schedl, P. (Genetics, 2004)
Drosophila melanogaster males have one X chromosome, while females have two. To compensate for the resulting disparity in X-linked gene expression between the two sexes, most genes from the male X chromosome are hyperactivated by a special dosage compensation system. Dosage compensation is achieved by a complex of at least six proteins and two noncoding RNAs that specifically associate with the male X. A central question is how the X chromosome is recognized. According to a current model, complexes initially assemble at approximately 35 chromatin entry sites on the X and then spread bidirectionally along the chromosome where they occupy hundreds of sites. Here, we report that mutations in Trithorax-like (Trl) lead to the loss of a single chromatin entry site on the X, male lethality, and mislocalization of dosage compensation complexes.